Contributions to the knowledge of hard ticks (Acari: Ixodidae) in Colombia - Rivera-Páez, Fredy A. [UNESP]; Labruna, Marcelo B.; Martins, Thiago F.; Perez, Jorge E.; Castaño-Villa, Gabriel J.; Ossa-López, Paula A.; Gil, Carlos A.; Sampieri, Bruno Rodrigues; Aricapa-Giraldo, Hector J.; Camargo-Mathias, Maria I. [UNESP] (Elsevier, 2018)
The known tick fauna of Colombia includes 58 species (15 Argasidae and 43 Ixodidae). To add to the knowledge of the biology of ticks in Colombia, hard ticks (Ixodidae) were collected from domestic animals or vegetation during 2014–2016 in 10 of Colombia's Departments. Ticks were identified to species through morphological examinations. Taxonomic identification was confirmed for some specimens by molecular methods, including phylogenetic analyses inferred from three tick genes (cytochrome c oxidase, 16S rDNA, second internal transcribed spacer). A total of 1745 tick specimens encompassing 8 species were collected. Overall, 5 tick species were recorded on cattle [Amblyomma dissimile, Amblyomma mixtum, Dermacentor nitens, Rhipicephalus microplus, Rhipicephalus sanguineus sensu lato (s.l.)], 5 on dogs (Amblyomma maculatum, Amblyomma ovale, Amblyomma varium, R. microplus, R. sanguineus s.l.), 3 on horses (A. mixtum, D. nitens, R. sanguineus s.l.), 3 on donkeys (A. mixtum, D. nitens, R. microplus), 1 on pig (D. nitens), and 2 from vegetation (A. mixtum, A. dissimile). This included the first records of A. mixtum from two Colombian Departments, indicating that the distribution of this tick in Colombia may be broader than currently known. Phylogenetic analyses confirmed that R. sanguineus s.l. specimens from 8 Departments belong to the “tropical species”. Moreover, Colombian specimens of A. maculatum formed a large clade with GenBank sequences of A. maculatum and A. triste, although some Colombian specimens grouped with A. maculatum from the United States while others grouped with A. triste from Brazil. Significant polymorphisms were observed between specimens of A. ovale or D. nitens; for the former species, it is noteworthy that two distinct clades were observed. Our study provides new records for 8 tick species parasitizing domestic animals in Colombia, including species with veterinary and medical importance in the Neotropical region, such as R. microplus, R. sanguineus, D. nitens, A. mixtum, and A. maculatum. Noteworthy, we provide the first record of A. varium infesting a domestic mammal.
Keywords: Amblyomma mixtum; Molecular analyses; Neotropical region; Rhipicephalus sanguineus